Legal Consequences of Marriage Agreement that is Made After The Marriage Exists for Husband and Wife Who Have Debts - Ade Izdihar, Raihan; Harahap, Burhanudin; Suryono, Arief (International Journal of Educational Research & Social Sciences, 2024)
Marriage is a physical and mental bond between a man and a woman, hereinafter referred to as husband and wife. In marriage, there are married couples who make a marriage agreement. The Constitutional Court issued Constitutional Court Decision Number 69/PUU-XIII/2015 which states that a marriage agreement can now be made after a marriage has taken place. Debt arising in a marriage is very possible, this can be done by both husband and wife. The result of this research is that liability cannot be asked of the husband and wife if the husband or wife does not first agree to a credit agreement with collateral for joint property. This type of research is normative research that uses a statutory approach and uses primary legal sources and secondary legal materials. The legal material analysis technique used is qualitative analysis, namely discussing the legal material that has been obtained by referring to the existing theoretical basis.